De Jure Versus De Facto Exchange Rate Regimes in Sub-Saharan Africa - Slavov, Slavi (IMF Working Papers; Working Paper ;, 2011)
There are 22 countries in Sub-Saharan Africa (SSA) with floating exchange rate regimes, de jure. Some target the money supply or the inflation rate; others practice "managed floating." Statistical analysis on monthly data for the past decade reveals that in most cases these exchange rate regimes can be approximated surprisingly well by a soft peg to a basket dominated by the US dollar. The weight on the dollar appears to have fallen somewhat across the continent in the aftermath of the global financial crisis. Replicating the model with weekly data for The Gambia suggests that the focus on the dollar might be even more pronounced at higher data frequencies. While there might be strong arguments in favor of limiting exchange rate volatility in SSA countries, soft-pegging to the dollar does not appear to be the best fit for them, given the currency structure of their external trade and finance. The paper concludes by discussing some policy options for SSA countries with flexible exchange rates, in the context of an illustrative recent country case.